IMPROVING STUDENTS’ WRITING SKILL OF RECOUNT TEXT THROUGH DIARY WRITING AT EIGHTH GRADE STUDENTS OF MTS NEGERI 2 PALU - Dhifa Olyevia; Nurdin; Ana Kuliahana; Hijrah Syam (Datokarama English Education Journal, 2021)
This research with a quantitative approach aims to determine whether the use of diary writing strategy is effective to improve writing skill in recount text of eighth grade students at MTS Negeri 2 Palu. The population in this research were students at MTS Negeri 2 Palu and the sample was students in grades VIII A and B with a total sample of 70 students. However, due to the pandemic ccovid-19with all the limitation, the researcher only obtained 24 students as the samples who took the test in this research. In this research the researcher used a purposive sampling technique. The data collection technique using test, namely pre-test and post- test. The technique of data analys is that the researcher used is the t-test. The results of the data analysis showed that t-count is and t-table (t-count10,632 > t-table1,796). It means the results of the research showed that there is improvement in the eighth grade students’ writing skill in recount text after the implementation of Diary writing strategy at MTS Negeri 2 Palu.